Concentração de flúor e cálcio no fluido do biofilme associada ao uso de dentifrícios fluoretados suplementados com trimetafosfato de sódio ou glicerofosfato de cálcio, sob desafio cariogênico - Nagata, Mariana Emi [UNESP] (2015)
Recent studies demonstrated that low fluoride dentifrices (LFD, 550 μg F/g) supplemented with calcium or phosphate have a similar effectiveness to a conventional dentifrice (CD, 1100 μg F/g). However, the mechanisms by which these compounds act on the de- and remineralization processes remain unclear. The present study evaluated fluoride (F) and calcium (Ca) concentrations in the biofilm fluid formed in situ under cariogenic challenge after using F dentifrices, supplemented or not with sodium trimetaphosphate (TMP) or calcium glycerophosphate (CaGP). Volunteers (n=12) were randomly divided into 5 groups according to the following toothpastes: Placebo (no F or CaGP, TMP), CD and LFD with no supplementation (550F) or supplemented with 1% TMP (550F-TMP) or 0.25% CaGP (550F-CaGP). In each phase, volunteers wore palatal appliances containing 4 bovine enamel blocks. The cariogenic challenge was produced using a 30% sucrose solution, 6 times a day. On the morning of the 8th day, biofilm samples were collected 1h and 12h after brushing and cariogenic challenge. F and Ca analyzes were performed with the inverted electrode after buffering with TISAB III and using the Arsenazo III method, respectively. Data were submitted to 2-way ANOVA (repeated measures) and Student-Newman-Keuls test (p<0.05). A dose-response relationship was verified between F concentrations in the dentifrices and those in the biofilm fluid. Significant differences were observed among Placebo, 550F and CD only 1 h after brushing, without statistical differences among 550F, 550F-TMP and 550F-CaGP. No defined trend was observed among the groups regarding Ca concentrations in the biofilm fluid, with the highest values found for Placebo and 500F-CaGP. It was concluded that the anticaries effects of LFDs supplemented with CaGP or TMP cannot be related to an increased availability of F and Ca in the biofilm fluid